On the presence of electric dipole and toroidal moments in non-Hermitian QED - R. Bufalo; Nathan B. Xavier (Physics Letters B)
We study in this paper non-relativistic properties of the non-hermitian and PT symmetric QED, in special the Pauli-Schrödinger Hamiltonian. It is shown that the scattering potential computed in terms of the Born approximation receives phenomenological modifications due to non-hermitian effects. In one side, we observe that the non-hermiticity changes the electric coupling as well as the magnetic coupling; on the other hand, and more important, the model induces two new types of phenomenological interactions: i) an electric dipole coupling and ii) a toroidal coupling. Under the light of these results, and also that the extraordinary agreement of the Standard Model with experiment nearly excludes any significant amount of non-Hermitian couplings, we establish an analysis for each coupling in terms of their experimental data to set stringent bounds upon the axial parameters of the non-hermitian model.